Increased Productivity of Regional Potential-based MSMEs through Partnership Development - Dirbawanto, Nana Dyki (Journal Business Administration: Entrepreneurship and Creative Industry, 2025)
The current existing condition in Labuhanbatu Regency, where the number and performance of SMEs are not yet competitive enough, especially in the digital market which currently holds significant influence in the buying and selling process of SME products. There is a need for further training related to digital transformation, considering that technology now plays a crucial role in SME development. This research aims to examine the average productivity index of SMEs in Labuhanbatu, the region’s potential, and partnership strategies in Labuhanbatu Regency. The study employs average index analysis using a perception measurement scale of 1-7 on 81 SMEs in Labuhanbatu and 8 local government organizations, as well as a SWOT analysis. Based on the Strengths, Weaknesses, Opportunities, and Threats analysis, SMEs in Labuhanbatu have strengths such as optimized production, adequate local potential, support programs for SMEs, and fairly good SME skills. Weaknesses include limited production support equipment and inadequate marketing networks. Opportunities for SMEs include the growth of SME industries, supportive skills training programs, improved communication, ease of licensing processes, and non-burdensome taxes for businesses. Meanwhile, threats include unstable product prices, inadequate financial support from local government, and insufficient marketing awareness efforts by the local government.